2024
DOI: 10.3389/fphar.2024.1365802
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic acid metabolism as a therapeutic target in AKI-to-CKD transition

Xiao-Jun Li,
Ping Suo,
Yan-Ni Wang
et al.

Abstract: Arachidonic acid (AA) is a main component of cell membrane lipids. AA is mainly metabolized by three enzymes: cyclooxygenase (COX), lipoxygenase (LOX) and cytochrome P450 (CYP450). Esterified AA is hydrolysed by phospholipase A2 into a free form that is further metabolized by COX, LOX and CYP450 to a wide range of bioactive mediators, including prostaglandins, lipoxins, thromboxanes, leukotrienes, hydroxyeicosatetraenoic acids and epoxyeicosatrienoic acids. Increased mitochondrial oxidative stress is considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 178 publications
0
1
0
Order By: Relevance
“…Prostaglandins such as PGE2 and PGF2α are metabolized by ARA by the COX-2 pathway [36]. We found that S. Typhimurium infection significantly increased the levels of COX-2 and PGF2α in HD11 cells and promoted the mRNA expression of inflammatory factors (IL-1β, IL-6, and iNOs).…”
Section: Discussionmentioning
confidence: 76%
“…Prostaglandins such as PGE2 and PGF2α are metabolized by ARA by the COX-2 pathway [36]. We found that S. Typhimurium infection significantly increased the levels of COX-2 and PGF2α in HD11 cells and promoted the mRNA expression of inflammatory factors (IL-1β, IL-6, and iNOs).…”
Section: Discussionmentioning
confidence: 76%